ANALISIS KESALAHAN NOLTING PADA SISWA DALAM MENGERJAKAN SOAL PERBANDINGAN TINGKAT SMP - Wibowo, Raka Naval Setia; Haerudin, Haerudin (LPPM Universitas Bina Bangsa, 2024)
Error is a mistake about something that was said to be correct in a previous agreement. Comparison is material that students still find difficult to understand in learning and many errors still occur. Even though the concept of comparative material is applied in everyday life, quite a lot of students have difficulty and do not understand comparative material. This research is descriptive research with a qualitative approach. Purposive sampling technique was used in this research to select samples with certain considerations. This research uses indicators of the types of Nolting errors, namely errors due to carelessness, errors in understanding concepts, errors in application, and errors in final results. The purpose of this research is to describe what errors experienced by students using the Nolting error type. Based on the results of the analysis carried out by researchers on careless mistakes, students were not careful enough to make mistakes that had an impact on the final results. In conceptual errors, students do not understand the formula so they cannot find a way to solve the problem. In application errors, students can know the formula but cannot apply it to the answer. Meanwhile, the final result is an error where the student is correct in the steps but does not answer what was asked in the question